La forza delle comunità locali Giacomo Becattini e la teoria della cultura sociale - Bellanca, Nicolò (Studi e saggi, 2023)
This book, inspired by the thought of Giacomo Becattini, reflects on why local communities continue to exist and spread. Why does the planet not become one place without borders? Why instead do we humans preferentially group ourselves into communities that are neither 'too wide' nor 'too narrow'? What characterizes today's form of community? Why are these communities rooted in places? What is peculiarly 'local' about places? Together with Becattini, we answer that the foundation of local communities is social culture. In its material and symbolic dimensions, social culture animates various forms of proximity between people and between groups: in addition to territorial proximity, social proximity (also online) and institutional proximity matter a lot. This implies that today a local community is not only a place where social culture makes us physically close, but where at least some of the major forms of proximity intersect.